PENGARUH LAMA PEMERAMAN DAN PENGASAPAN TERHADAP KUALITAS KIMIA DAN ASPEK ORGANOLEPTIK DAGING AYAM BROILER ASAP - Arkhimedes Eduard Lakapu; Gemini E.M Malelak; Bastari Sabtu (JURNAL NUKLEUS PETERNAKAN, 2017)
Aims of this research were to know the influence of curing and smoking time on water, protein, fat, and cholesterol content, water holding capacity, and organoleptic aspect of smoked broiler chicken. The research followed completely randomized design (3x3) with factorial pattern. Factor A was curing time 8, 16 and 24 hours, and factor B was smoking time 60, 90, and 120 minutes. The result of this research showed that curing or smoking time influenced the fat and cholesterol content (P<0.05), the protein content was influenced by the smoking time (P<0.05). Water content, water holding capacity and organoleptic aspect were not influenced by curing and smoking time. The lowest fat and cholesterol content was obtained at 24 hours curing time. The highest protein content was obtained at 60 minutes of smoking time. The lowest fat content was obtained at 60 minutes of smoking time, the lowest cholesterol content was obtained at 120 minutes of smoke time. The combination of curing and smoking time influenced on fat and cholesterol content (<0.05). The lowest fat content was obtained at 24 hours curing and 60 minutes smoking time. The lowest cholesterol content was obtained at 24 hours curing and 120 minutes smoking time. In conclusion as curing time increase, fat and cholesterol are decrease. As smoking time increases, protein and cholesterol decreases. ABSTRAK Tujuan penelitian adalah untuk mengetahui pengaruh lama pemeraman dan pengasapan terhadap kadar air, protein, lemak, kolesterol, dan daya ikat air, serta aspek organoleptik daging ayam broiler asap. Rancangan yang digunakan adalah Rancangan Acak Lengkap (RAL) pola faktorial (3x3). Faktor A: lama pemeraman selama 8, 16 dan 24 jam, faktor B: lama pengasapan selama 60, 90, dan 120 menit. Hasil penelitian ini menunjukkan bahwa faktor lama pemeraman atau pengasapan mempengaruhi kadar lemak dan kolesterol daging ayam broiler asap (P<0.05), sedangkan kadar protein hanya dipengaruhi oleh faktor lama pengasapan (P<0.05). Kadar air, daya ikat air, serta aspek organoleptik tidak dipengaruhi oleh faktor pemeraman atau pengasapan. Kadar lemak dan kolesterol terendah pada pemeraman selama 24 jam. Kadar protein tertinggi diperoleh pada pengasapan 60 menit. Kadar lemak terendah diperoleh pada pengasapan 60 menit, kadar kolesterol terendah diperoleh pada pengasapan 120 menit. Kombinasi perlakuan lama pemeraman dan pengasapan mempengaruhi kadar lemak dan kolesterol daging ayam broiler asap (P < 0.05). Kadar lemak terendah diperoleh pada pemeraman 24 jam dan pengasapan 60 menit. Kadar kolesterol terendah diperoleh pada pemeraman 24 jam dan pengasapan 120 menit. Semakin lama pemeraman, semakin menurunkan kadar lemak dan kolesterol. Semakin lama pengasapan, semakin rendah kadar protein dan kolesterol.